2005
DOI: 10.1145/1042091.1042093
|View full text |Cite
|
Sign up to set email alerts
|

Trust in e-commerce

Abstract: Web-based businesses succeed by cultivating consumers' trust, starting with their beliefs, attitudes, intentions, and willingness to perform transactions at Web sites and with the organizations behind them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(102 citation statements)
references
References 11 publications
(21 reference statements)
0
83
1
2
Order By: Relevance
“…Cheung and Lee (2001) indicated that perceived security control and perceived privacy control are critical characteristics of online transactions affecting the development of online consumers' confidence on e-commerce. Salam et al (2005) viewed trust as a complex social phenomenon reflecting technological, behavioural, social, psychological and organisational interactions among human and non-human (technological) agents. The authors write (p.77):…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cheung and Lee (2001) indicated that perceived security control and perceived privacy control are critical characteristics of online transactions affecting the development of online consumers' confidence on e-commerce. Salam et al (2005) viewed trust as a complex social phenomenon reflecting technological, behavioural, social, psychological and organisational interactions among human and non-human (technological) agents. The authors write (p.77):…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of online economic exchanges, some customers display a greater disposition to trust anything and anybody and are more likely to trust a web vendor despite having only limited information about it, whereas others need more information to form trusting beliefs (Salam, Iyer, Palvia, & Singh, 2005). However, empirical studies on the impact of propensity to trust on the formation of online trust yielded conflicting results.…”
Section: Propensity To Trustmentioning
confidence: 99%
“…Such variations in trust propensity or disposition, referring to the tendency to be willing to depend on others across a broad spectrum of situations and persons (McKnight, Choudhoury, & Kacmar, 2002;McKnight, Cummings, & Chervany, 1998) are also evident in online economic exchanges wherein some people would display a greater disposition to trust anything and anybody and are more likely to trust online entities despite having limited information about them, while others would require more information about the trust target before deciding to trust (Salam et al, 2005). Low levels of trust propensity could be assumed to eventuate in minimal trusting decisions, while high levels of trust propensity could propel an increase in trusting decisions.…”
Section: Trust Propensitymentioning
confidence: 99%
“…Adaptations must be made to attitudes and values in addition to product capabilities or organizational practices. Therefore, product suppliers can build mutually valuable relationships with retailers through a trust-based collaboration process 45 . However, the manner in which trust is gained and its effect on e-business outcomes remain unclear 46 .…”
Section: International Journal Of Electronic Commerce Studies 246mentioning
confidence: 99%